Transformational Leadership Dalam Industri Asuransi: Strategi Peningkatan Kinerja Perusahaan Melalui Inovasi, Pengembangan SDM, dan Pendidikan Organisasional - Terminanto, Ade Ananto; Haryanti, Enny; Megawati; Nurwiatin, Neng; Harini, Hegar (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine the role of transformational leadership in improving the performance of insurance companies through innovation strategies, human resource development, and organisational education. This research uses a literature review method with a qualitative approach, where data is analysed using thematic descriptive analysis techniques. Data were collected from scientific articles published between 1978-2025 and obtained from Google Scholar and trusted academic sites. Of the 50 articles reviewed, 33 were selected through rigorous selection based on their relevance, methodological quality, and contribution to the research topic. The results showed that transformational leaders play a role in fostering an innovative culture, increasing human resource capacity through continuous training, and building an organisational education system that is adaptive to industry changes. Previous studies also support that this leadership style is able to improve company performance in terms of financial, operational, and employee satisfaction.